POTENTIAL OF JAMBLANG (Syzygium cumini L.) LEAF EXTRACT ON BODY WEIGHT OF WISTAR RATS METABOLIC SYNDROME MODEL - Ida Nurwati; Risya Cilmiaty AR; Danus Hermawan; Betty Saptiwi; Dyah Ratna Budiani; Jarot Subandono; Martini Martini; Muthmainah Muthmainah; Sarsono Sarsono; Selfi Handayani (Jurnal Riset Kesehatan, 2021)
Jamblang (Syzygium cumini L.) leaves contain several phytochemical compounds. These phytochemicals are thought to have roles as antihyperglycemic, antihyperlipidemic, and antioxidant agents. This study aims to prove that there is an effect of giving ethanolic extract of jamblang leaves on body weight (BW) of metabolic syndrome (MS) Wistar rats induced by high-fat high-fructrose diet (HFFD) and injection of Streptozotocin (STZ)-Nicotinamide (Na), to determine different doses effect on the weight of Wistar rats. Laboratory experimental research with pre-post test control group. Samples were 8 weeks male Wistar (Rattus noverigicus) weighing 150-200 grams chosen by purposive random sampling method. Thirty rats were divided into 5 groups, each consisting of 6 rats. Normal group, metabolic syndrome group, 3 treatment groups MS were given jamblang leaf extract 100 mg/KgBW, 150mg/KgBW, 200mg/KgBW for 28 days. Data were analyzed by one way ANOVA test and repeated ANOVA test. The study showed an ethanolic extract of Jamblang leaves can reduce weight loss in Wistar rats with a metabolic syndrome model, and that the best dose used in this experiment is 150 mg/kgBW per day in Wistar rats with a metabolic syndrome model.